DIFFERENTIATED ENGLISH MATERIALS AND FIFTH-GRADE STUDENTS' LISTENING COMPREHENSION: A QUASI-EXPERIMENTAL STUDY - I Made Bhanu Aditya Parameswara; Ni Wayan Surya Mahayanti; Luh Putu Dian Kresnawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The diversity of learning characteristics among elementary school students presents a considerable challenge in English instruction, particularly in developing listening comprehension, which requires gradual and sustained exposure to spoken language. This condition has encouraged the use of differentiated English materials as an instructional alternative aligned with the implementation of the Merdeka Curriculum, aiming to provide learning experiences that are more responsive to students' diverse needs. To obtain empirical evidence regarding their effectiveness, this study involved 60 fifth-grade students from SD Negeri 1 Banyuasri, who were assigned to an experimental group and a control group using a quasi-experimental pretest–posttest control group design. The experimental group received instruction supported by differentiated English materials, whereas the control group learned through conventional instructional materials. Data were collected using a validated listening comprehension test. Preliminary assumption testing indicated that the data did not fully satisfy the normality assumption; therefore, differences between the two groups were analyzed using the non-parametric Mann–Whitney U test. Although the post-test mean scores of both groups increased compared with their pre-test scores, the inferential analysis revealed no statistically significant difference in learning outcomes (p = .809). These findings contribute to the growing body of empirical evidence on the implementation of Differentiated Instruction in elementary English education by demonstrating that the effectiveness of differentiated English materials depends on the integration of instructional strategies, sustained listening practice, and effective teacher facilitation, rather than solely on the availability of differentiated instructional materials. ABSTRAK Keragaman karakteristik belajar siswa sekolah dasar menghadirkan tantangan tersendiri dalam pembelajaran English, terutama pada pengembangan kemampuan listening comprehension yang memerlukan paparan bahasa lisan secara bertahap dan berkelanjutan. Kondisi tersebut mendorong pemanfaatan differentiated English materials sebagai salah satu alternatif yang sejalan dengan implementasi Merdeka Curriculum, dengan tujuan memberikan pengalaman belajar yang lebih responsif terhadap kebutuhan peserta didik. Untuk memperoleh bukti empiris mengenai efektivitasnya, penelitian ini melibatkan 60 siswa kelas V SD Negeri 1 Banyuasri yang terbagi ke dalam kelompok eksperimen dan kelompok kontrol menggunakan desain quasi-experimental pretest–posttest control group. Kelompok eksperimen mengikuti pembelajaran berbantuan differentiated English materials, sedangkan kelompok kontrol menggunakan materi konvensional. Data diperoleh melalui tes listening comprehension yang telah melalui proses validasi. Hasil pengujian prasyarat menunjukkan bahwa distribusi data belum sepenuhnya memenuhi asumsi normalitas sehingga analisis perbedaan antarkelompok dilakukan menggunakan uji nonparametrik Mann–Whitney U. Meskipun rerata skor post-test kedua kelompok mengalami peningkatan dibandingkan pre-test, analisis inferensial menunjukkan bahwa perbedaan hasil belajar tidak signifikan (p = 0,809). Temuan ini memperkaya bukti empiris mengenai implementasi Differentiated Instruction pada pembelajaran English di sekolah dasar dengan menunjukkan bahwa keberhasilan penggunaan differentiated English materials bergantung pada integrasi strategi pembelajaran, keberlanjutan latihan listening, serta kualitas fasilitasi guru, bukan semata-mata pada penyediaan bahan ajar yang terdiferensiasi.